The Value of the Antibody Detection in the Diagnosis of Ocular Toxocariasis and the Aqueous Cytokine Profile Associated With the Condition - Zhang, Xiang; Yang, Yuan; Zheng, Yan; Hu, Yiqian; Rao, Yuqing; Li, Jiakai; Zhao, Peiquan; Li, Jing (Frontiers in Medicine, 2022)
Introduction: To evaluate and compare the specificity of Toxocara Canis-specific antibody detection in the serum and aqueous samples for the diagnosis of ocular toxocariasis (OT) and explore the cytokine profiles associated with the condition in children. Materials and Methods: This is a prospective cohort study. The inclusion criteria was the clinical presentations of OT, which included unilateral vision reduction, typical peripheral or posterior pole granuloma with variable degrees of vitritis, and exclusion of other diagnosis. The titer of antibody against the excretory-secretory antigen of Toxocara canis (T-IgG) was measured in serum and aqueous samples taken from the affected eyes. The diagnosis of OT was made upon positive detection of T-IgG either in the serum or aqueous. The rest with typical clinical presentations like OT as described above but a positive serum or aqueous T-IgG could not be confirmed were diagnosed as suspected-OT. Cytokines were measured using multiplexed cytometric bead array system. Results: Two hundred eleven eyes of 211 patients participated in the study. One hundred and twenty-eight eyes were diagnosed as OT. The median age of the cohort was 7.7-years with a male to female ratio of 2.5:1. Major initial symptoms were decreased vision (74%) and strabismus (22%). The percentage of eyes with peripheral granuloma, posterior granuloma and endophthalmitis were 40%, 18% and 41%, respectively. Vitritis (100%), vitreous strands (64%), retinal fibrotic bands (57%), and retinal detachment (42%) were most common signs. T-IgG was positive in 66.7% of the aqueous and 57.2% of the serum samples. Forty-four patients were T-IgG negative in both serum and aqueous of the affected eyes. IL-6, MCP-1, IL-8, Eotaxin, MCP-1β and VEGF were higher in T-IgG negative eyes compared to controls and further increased in T-IgG positive eyes. However, only T-IgG positive eyes showed increased IL-5, IL-13 and IL-10. IL-1, TNF-α, IL-12, IL-2, IFN-γ and IL-4 were undetectable in all eyes. Conclusions: Pediatric OT often present with severe retinal complications. Polarized intraocular Th2 response was only found in aqueous T-IgG-positive eyes. Our results supported aqueous sample-based antibody test for the more specific diagnosis of OT.